CaMKII Mediates Recruitment and Activation of the Deubiquitinase CYLD at the Postsynaptic Density - Thein, Soe (Public Library of Science, 2014)
NMDA treatment of cultured hippocampal neurons causes recruitment of CYLD, as well as CaMKII, to the postsynaptic density (PSD), as shown by immunoelectron microscopy. Recruitment of CYLD, a deubiquitinase specific for K63-linked polyubiquitins, is blocked by pre-treatment with tatCN21, a CaMKII inhibitor, at a concentration that inhibits the translocation of CaMKII to the PSD. Furthermore, CaMKII co-immunoprecipitates with CYLD from solubilized PSD fractions, indicating an association between the proteins. Purified CaMKII phosphorylates CYLD on at least three residues (S-362, S-418, and S-772 on the human CYLD protein Q9NQC7-1) and promotes its deubiquitinase activity. Activation of CaMKII in isolated PSDs promotes phosphorylation of CYLD on the same residues and also enhances endogenous deubiquitinase activity specific for K63-linked polyubiquitins. Since K63-linked polyubiquitin conjugation to proteins inhibits their interaction with proteasomes, CaMKII-mediated recruitment and upregulation of CYLD is expected to remove K63-linked polyubiquitins and facilitate proteasomal degradation at the PSD.